Self-assembled Co3O4 hexagonal plates by solvent engineering and their dramatically enhanced electrochemical performance. Issue 2 (21st December 2016) - Zhao, W.; Zhou, X.; Kim, I. Jin; Kim, S.
Abstract : Self-assembly of primary nanocrystals provides new insight into manipulating the crystal plane structure for energy applications. Abstract : In this study, a facile two-phase solvothermal method was used to synthesize Co3 O4 nanocubes with high crystallinity and narrow size distribution (∼49 nm) for use in lithium-ion batteries. Here, oleylamine (OAm) was chosen as the solvent, surfactant, and reducing agent. After washing with the appropriate organic solvent, the Co3 O4 nanocubes self-assembled into hexagonal plates with a diameter and thickness of approximately 2.5 μm and 550 nm, respectively. Moreover, with the assistance of dipole–dipole and van der Waals interactions, the Co3 O4 nanocubes stacked along the [111] direction with their exposed facets attached, leading to their final exposed cross-sectional facet being (111). A possible assembling mechanism is proposed and explained in detail. Furthermore, the self-assembled (111) faceted Co3 O4 plates exhibited superior electrochemical capacity and stability to those original (001) faceted Co3 O4 nanocubes for Li + ion storage. Therefore, the solvent engineered self-assembly into secondary structures has proven to be a potential strategy for energy applications.